Optimization of heterogeneous Fenton-like process with Cu-Fe@CTS as catalyst for degradation of organic matter in leachate concentrate and degradation mechanism research. (October 2021) - Guo, Chengrui; Qin, Xia; Guo, Rui; Lv, Yue; Li, Mingran; Wang, Ziyuan; Li, Tinghui
Highlights: The pre-coagulated landfill leachate concentrate was treated by Fenton-like process. Process parameters were optimized by BBD of RSM. The OH radical proved to be the main active species. The Fenton-like system produced more OH at pH of 4. The stability of the Fenton-like process under different pH was explored. Abstract: The heterogeneous Fenton-like process with bimetallic chelated magnetic chitosan aerogel (Cu-Fe@CTS) as catalyst was applied to treat pre-coagulated leachate nanofiltration concentrate. The process conditions were optimized by Box-Behnken Design (BBD) and the maximum UV254 removal reached 96.06% under the conditions of temperature 87.62 °C, oxidant dosage 0.2395 mol/L and catalyst dosage 1 g/L. The TOC concentration was reduced from 847.5 to 99.7 mg/L and COD concentration was reduced from 1625 to 464 mg/L. The three-dimensional (3D) fluorescence analysis showed that most of Fulvic acid-like (FA-like) was removed. The adsorption experiment showed that the catalyst reached the adsorption balanced after 60 min and the corresponding FA adsorption removal reached 14.1%. The addition of Tert-butanol (TBA) reduced the FA removal by 59.4%, indicating that the hydroxyl radicals ( OH) was the main active species. Experiments of the OH capture at different pH showed that the Fenton-like system produced more OH at pH of 4, at which the maximum FA removal was 96.61%, while the FA removal still reached 94.26% at pH of 7. The OH capture at different temperature showed that the Fenton-like system produced more OH at 90 °C. KI and TBA shielding experiments showed that OH was produced on the catalyst surface rather than being produced by catalysis of free metal ions in the solution.